Hind limb perconditioning renoprotection by modulation of inflammatory cytokines after renal ischemia/reperfusion. (27th May 2016) - Sedaghat, Zahra; Kadkhodaee, Mehri; Seifi, Behjat; Salehi, Eisa
Abstract: Purpose Renal ischemia/reperfusion (I/R) injury is a common clinical problem associated with significant mortality and morbidity. One newly described strategy to reduce this damage is remote perconditioning (RPEC), in which short-time ischemia of a limb during renal ischemia reduces the I/R-induced kidney injury. This study aimed to assess whether RPEC confer protection through changes in pro-inflammatory mediators.Methods Rats were subjected to right nephrectomy and randomized into: sham (no intervention), I/R (subjected to 45-min left renal ischemia) and RPEC group (subjected to four cycles of 5-min I/R of the femoral artery administered during renal ischemia). After 24-h, blood, urine, and kidney samples were collected. Biochemical indicators of renal dysfunction were measured in the cases of Neutrophil gelatinase-associated lipocalin (NGAL), and N-acetyl-B-diglucosaminidase (NAG) activity. Inflammatory cytokines [interleukin (IL)-6 and tumor necrosis factor-alpha, TNF-α] expression in the renal tissues as well as Periodic acid-Schiff stained histological sections were evaluated.Results I/R resulted in renal dysfunction, as evidenced by higher renal NGAL expression and urinary NAG activities. This was accompanied by increased TNF-α and IL-6 expressions as well as histological changes in this group. However, RPEC improved renal histology and function compared with the I/R group. Furthermore, the RPEC group showed decreases in TNF-α and IL-6 expression.Conclusions These results suggest that RPEC reduces the dysfunction and injury associated with I/R of the kidney. This technique reduced the pro-inflammatory cytokine in the kidney. RPEC could be a promising strategy against I/R-induced acute kidney injury partly by down-regulation of inflammatory mediators.